Rechallenge with Amisulpride in a Patient with Schizophrenia following a Manic Episode during Previous Therapy - Hu, Li-Yu; Hong, Chen-Jee; Tsai, Shih-Jen; Shen, Cheng-Che (Case Reports in Psychiatry, 2022)
Amisulpride is an atypical antipsychotic. It is also effective in treating depression. The potential antidepressant effect raises the concern that amisulpride can induce mania. However, reports of amisulpride-induced mania have been rare. Here, we present the case of a Taiwanese woman with a 22-year history of schizophrenia. At the age 57 years, she developed manic symptoms while on treatment with amisulpride for six weeks. She was immediately admitted to the psychiatric in-patient unit. The manic symptoms completely subsided within eight days without the administration of any mood stabilizer. Readministration of a single dose of 200 mg amisulpride during hospitalization induced the same manic symptoms, which remitted completely within 24 hours without any mood stabilizer administration.